KEBIJAKAN MORATORIUM PENGIRIMAN TENAGA KERJA INDONESIA KE MALAYSIA 2009 - Srimala Sari B (2012)

(untitled)
Cooperation between Indonesia-Malaysia had already happened since Soekarno administration. Indonesia and Malaysia, which have similarity such as majority of Muslim society and Malay race, make them as neighbors who need each other. Indeed, the cooperation does not away from conflict such as conflict of border, ownership and also labor. But, the conflict cannot remove the good relation between those countries. They can maintain good relation through soft and peace diplomacy in solving the conflic